BREAKFASTLOVE : Perfect little bowls of quick, healthy breakfasts - Bez, David (London : Quadrille, 2016)
"Breakfast Love contains more than 160 bowls for healthy, speedy breakfast ideas that will set you up for the day. Breakfast Love will make you fall in love with this often over-looked meal, and energize you to create a beautiful bowl of breakfast salad before you start the day. Each bowl is made up of a base of grains, two seasonal fruit and vegetables, some protein, a delicious dressing, yogurt or milk, and an optional topping. There are sweet and savory ideas, and basic recipes to make your own granola, muesli, and dairy-free nut 'yogurt'. Every recipe is categorized as vegan, vegetarian, raw, carnivore, or omnivore so that you can cater to your own dietary preference. With a stunning photo of every recipe, this is a feast for the eyes and fantastically inspiring."--Provided by Amazon.com
Introduction. The need for a better breakfast -- Anatomy of breakfast -- Fruits -- Vegetables -- Cereal -- Protein -- Toppings -- "Dressing" -- Better breakfasts -- t
Includes index
Keywords: Breakfasts; Brunches; Cookbooks